Gellan gum-hyaluronic acid spongy-like hydrogels and cells from adipose tissue synergize promoting neoskin vascularization - Cerqueira, Mariana Teixeira (2014)
Currently available substitutes for skin wound healing often result in the formation of nonfunctional neotissue. Thus, urgent care is still needed to promote an effective and complete regeneration. To meet this need, we proposed the assembling of a construct that takes advantage of cell-adhesive gellan gum-hyaluronic acid (GG-HA) spongy-like hydrogels and a powerful cell-machinery obtained from adipose tissue, human adipose stem cells (hASCs), and microvascular endothelial cells (hAMECs). In addition to a cell-adhesive character, GG-HA spongy-like hydrogels overpass limitations of traditional hydrogels, such as reduced physical stability and limited manipulation, due to improved microstructural arrangement characterized by pore wall thickening and increased mean pore size. The proposed constructs combining cellular mediators of the healing process within the spongy-like hydrogels that intend to recapitulate skin matrix aim to promote neoskin vascularization. Stable and off-the-shelf dried GG-HA polymeric networks, rapidly rehydrated at the time of cell seeding then depicting features of both sponges and hydrogels, enabled the natural cell entrapment/encapsulation and attachment supported by cell-polymer interactions. Upon transplantation into mice full-thickness excisional wounds, GG-HA spongy-like hydrogels absorbed the early inflammatory cell infiltrate and led to the formation of a dense granulation tissue. Consequently, spongy-like hydrogel degradation was observed, and progressive wound closure, re-epithelialization, and matrix remodelling was improved in relation to the control condition. More importantly, GG-HA spongy-like hydrogels promoted a superior neovascularization, which was enhanced in the presence of human hAMECs, also found in the formed neovessels. These observations highlight the successful integration of a valuable matrix and prevascularization cues to target angiogenesis/neovascularization in skin full-thickness excisional wounds.